1994
DOI: 10.1038/ki.1994.276
|View full text |Cite
|
Sign up to set email alerts
|

The calcemic response to PTH in the rat: Effect of elevated PTH levels and uremia

Abstract: Secondary hyperparathyroidism (2 degrees HPT) is a consistent finding in renal failure. A decreased calcemic response (CR) to parathyroid hormone (PTH) contributes to the development of 2 degrees HPT. Since parathyroidectomy (PTX) corrects the decreased CR to PTH in azotemic animals, down-regulation of PTH receptors induced by an elevation of PTH has been advanced as an important factor in the development of 2 degrees HPT. The goal of the study was to determine in azotemic rats whether a progressive reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…In patients and animals with kidney failure, secondary hyperparathyroidism develops and serum PTH levels may exceed 100 pM (Bover et al 1994, de Francisco 2004. Transgenic mice with parathyroid-targeted overexpression of cyclin D1 exhibit mild hyperparathyroidism, with PTH ranging between 13 and 16 pM -3-4-fold higher than their age-matched wild-type littermates (2-4 pM) -and a 20-30% increase in total serum calcium (Imanishi et a.…”
Section: Discussionmentioning
confidence: 99%
“…In patients and animals with kidney failure, secondary hyperparathyroidism develops and serum PTH levels may exceed 100 pM (Bover et al 1994, de Francisco 2004. Transgenic mice with parathyroid-targeted overexpression of cyclin D1 exhibit mild hyperparathyroidism, with PTH ranging between 13 and 16 pM -3-4-fold higher than their age-matched wild-type littermates (2-4 pM) -and a 20-30% increase in total serum calcium (Imanishi et a.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in normal and azotemic rats have shown that high dietary phosphate greatly increases PTH values (15,40). Conversely, dietary phosphate restriction reduces PTH values in normal rats and minimizes increases in PTH values in azotemic rats (13,41). Even in normal rats and humans who are given a single meal that contains a high phosphate content, it has been shown that postprandial PTH values increase (42)(43)(44).…”
Section: Basal Pthmentioning
confidence: 99%
“…Massry et al [15] demonstrated a reduced calcemic response to infusion of parathyroid extract to 105 subjects with varying degrees of renal failure. A diminished calcemic response to PTH in chronic kidney disease has also been demonstrated in animal studies [16][17][18][19][20][21][22][23][24], and using dogs with chronic kidney disease, Galceran et al [24] found that the calcemic response to PTH was restored following parathyroidectomy. Furthermore, a blunted cAMP response to PTH extract was observed by Olgaard et al [25] in isolated perfused bones obtained from uremic dogs.…”
Section: Discussionmentioning
confidence: 88%